University life in Singapore : stressors and its coping strategies. - Tay, Nicole Zhu Han. (2011)
This study seeks to find out how university life is like for undergraduates in Singapore. It will focus on the stressors that the undergraduates are faced with and how they go about coping with them. From the results, it can be seen that issues pertaining to the lack of control, pressure from one’s social network and time constraints, factor heavily into contributing stress for the respondents due to the postmodern society that we are living in. As for the type of coping strategies that are being employed, on top of using their social network as a form of social support, respondents were found to utilize their multiphrenia as another way of coping.